1996
DOI: 10.1182/blood.v87.5.1746.1746
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the erythropoietin-induced erythroid differentiation by granulocyte-macrophage colony-stimulating factor in the human UT-7 cell line is not due to a negative regulation of the erythropoietin receptor

Abstract: The human pluripotent UT-7 cell line is growth factor-dependent for proliferation and differentiation. We have previously shown that (1) granulocyte-macrophage colony-stimulating factor (GM-CSF) and erythropoietin (Epo) induce a myeloid and erythroid pattern of differentiation, respectively; (2) GM-CSF acts predominantly over Epo for cell differentiation; (3) GM-CSF induces a rapid downmodulation (4 hours) of Epo receptors (Epo-R) at the mRNA and binding site levels; and (4) in contrast, Epo has no effect on G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
1
7
0
1
Order By: Relevance
“…Most cytotoxic chemotherapeutic drugs cause apoptosis in cancer cells. However, certain tumor cells often escape apoptosis by overexpressing antiapoptotic proteins such as Bcl-2, NF-κB, and Akt [ 12 - 14 ]. Despite advances in surgery and chemotherapy, the survival rate of patients with ovarian cancer is still low because of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Most cytotoxic chemotherapeutic drugs cause apoptosis in cancer cells. However, certain tumor cells often escape apoptosis by overexpressing antiapoptotic proteins such as Bcl-2, NF-κB, and Akt [ 12 - 14 ]. Despite advances in surgery and chemotherapy, the survival rate of patients with ovarian cancer is still low because of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A competition between EPO and GM-CSF has been reported in cells of the marrow [ 33 ]. In addition, it has been shown that GM-CSF can modulate EPO effects in certain leukemic cell line models of hematopoiesis, modulating events at the transcriptional and signal transduction level, or decreasing mRNA levels of EPO receptor [ 34 ]. Finally concentrations of hemopoietins have been found to play a key role in the final effect on cellular response [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, it is well known that even on erythroid precursor cells the number of EpoR expressed at the cell surface is extremely low [25]. Second, Epo receptors regularly circle from the cell surface to the cyto-plasm, depending on various factors such as the ambient Epo concentration [26,27]. In this regard it is possible that the Epo present in FCS binds to the cell EpoR, and therefore no available binding sites remain at the cell surface.…”
Section: Discussionmentioning
confidence: 99%